2005
DOI: 10.1161/01.str.0000149623.24906.63
|View full text |Cite
|
Sign up to set email alerts
|

Functional Electrical Stimulation Improves Motor Recovery of the Lower Extremity and Walking Ability of Subjects With First Acute Stroke

Abstract: Background and Purpose-The effectiveness of functional electrical stimulation (FES) has been investigated in chronic hemiplegia. The present study examines whether FES, given during acute stroke, was more effective in promoting motor recovery of the lower extremity and walking ability than standard rehabilitation alone. Methods-Forty-six subjects, 70.9Ϯ8.0 years old and 9.2Ϯ4.1 days after stroke, were assigned randomly to 1 of 3 groups receiving standard rehabilitation with FES or placebo stimulation or alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
198
2
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(208 citation statements)
references
References 21 publications
3
198
2
5
Order By: Relevance
“…Small trials have shown modest clinical improvement in disabilities after stroke with the use of the following techniques: electrical stimulation over the surface of muscles to contract them for simple movements, such as grasping, or to assist ankle dorsiflexion while walking 49 ; intense practice with electromechanical devices that assist in reaching or stepping 50 ; noninvasive stimulation of the peripheral nerve of the arm 51 or direct stimulation of the motor cortex over the hand representation 52 to augment cortical plasticity and learning during arm therapies; pharmacotherapy with agonists of dopamine, acetylcholine, and serotonin, which may modulate neurotransmission and learning 53 ; and the use of mental imagery of an action, 54 which may enhance training because it activates many of the same cortical neurons that are involved in performing the action. Phase 1 trials are beginning in order to assess the safety of the injection of drugs into the cerebrospinal fluid or of cells into brain tissue to replace neurons and promote dendrite sprouting and axon regeneration, 55 with the goal of possible neural repair.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Small trials have shown modest clinical improvement in disabilities after stroke with the use of the following techniques: electrical stimulation over the surface of muscles to contract them for simple movements, such as grasping, or to assist ankle dorsiflexion while walking 49 ; intense practice with electromechanical devices that assist in reaching or stepping 50 ; noninvasive stimulation of the peripheral nerve of the arm 51 or direct stimulation of the motor cortex over the hand representation 52 to augment cortical plasticity and learning during arm therapies; pharmacotherapy with agonists of dopamine, acetylcholine, and serotonin, which may modulate neurotransmission and learning 53 ; and the use of mental imagery of an action, 54 which may enhance training because it activates many of the same cortical neurons that are involved in performing the action. Phase 1 trials are beginning in order to assess the safety of the injection of drugs into the cerebrospinal fluid or of cells into brain tissue to replace neurons and promote dendrite sprouting and axon regeneration, 55 with the goal of possible neural repair.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Improvement of muscle strengthening and prevention of muscle atrophy have been reported for over 30 years. Improvement in motor and walking ability [2], [3], a possibility of improving gait pattern [3], and motor recovery of upper limb [4] have also been reported as the therapeutic effects of FES. Furthermore, FES therapy has been found to reduce disability and improve voluntary grasping beyond the effects of conventional upper extremity therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential benefits of applying FES early after stroke may include an ability to walk earlier, increased functional independence, earlier discharge home and improved motor recovery which may reduce the requirement for long-term use of FES or any orthotic device . (Taylor et al, 1999a;Yan, Hui-Chan and Li, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of research may be linked to the complexity of applying FES during the early stages after stroke or the difficulty of assessing its impact beyond that of routine recovery [Wade, 2009]. At present; only two studies have investigated the application of FES in acute stroke populations (< 2 weeks post stroke) [Kottink et al, 2004;Yan, Hui-Chan and Li, 2005;NICE 2008;Dunning et al, 2009] with no studies exclusively investigating FES during the subacute phase of stroke (two weeks to six months post stroke) [Kottink et al, 2004]. Yan, Hui-Chan and Li, 2005, undertook a trial with 46 participants, on average 10 days after stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation